2018
DOI: 10.3389/fncel.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of Alpha-Synuclein Influences on Alpha-Synuclein Aggregation Induced by Methamphetamine

Abstract: Methamphetamine (METH) is an illegal and widely abused psychoactive stimulant. METH abusers are at high risk of neurodegenerative disorders, including Parkinson’s disease (PD). Previous studies have demonstrated that METH causes alpha-synuclein (α-syn) aggregation in the both laboratory animal and human. In this study, exposure to high METH doses increased the expression of α-syn and the small ubiquitin-related modifier 1 (SUMO-1). Therefore, we hypothesized that SUMOylation of α-syn is involved in high-dose M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 71 publications
4
14
0
Order By: Relevance
“…Fibrils rapidly aggregate into insoluble macromolecules to form LBs (Auluck, Chan, Trojanowski, Lee, & Bonini, ). In the study, we verified that the level of α‐syn increases with increasing METH concentration and exposure time, which is consistent with previous studies (Qiao et al, ; Zhu et al, ). The accumulation of α‐syn can lead to apoptosis and even death of neurons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fibrils rapidly aggregate into insoluble macromolecules to form LBs (Auluck, Chan, Trojanowski, Lee, & Bonini, ). In the study, we verified that the level of α‐syn increases with increasing METH concentration and exposure time, which is consistent with previous studies (Qiao et al, ; Zhu et al, ). The accumulation of α‐syn can lead to apoptosis and even death of neurons.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, α‐syn is considered to be a protein closely related to neurodegenerative diseases (e.g., Parkinson's disease [PD] and Alzheimer's disease [AD]) (Henderson et al, ; Twohig & Nielsen, ). Previous studies, including studies by our research group, have found that α‐syn expression and the degree of cell injury increase with increasing METH concentrations (Biagioni et al, ; Qiao et al, ; Sun et al, ; Wang et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Taken together, our results strongly support the report by Krumova et al (2011) that SUMOylated α-syn promotes its solubility, prevents protein aggregation and further, reduces cytotoxicity in the SNpc. Our findings also support the recent publication that METH exposure reduces the level of SUMOylation on α-syn, and METH-induced α-syn aggregation is relieved by Ubc9 overexpression ( Zhu et al, 2018 ). The study has also demonstrated that mutations in SUMOylation acceptor sites in α-syn enhance α-syn overexpression and aggregation induced by METH, which is mediated by impaired degradation through the UPS and the ALP in vitro and in vivo ( Zhu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, UBC9 overexpression was reported to increase the solubility of α-syn and prevent methamphetamine (METH)-induced protein aggregation. Further, non-SUMO α-syn mutants enhance their aggregation by impairing proteasomal and lysosomal degradation ( Zhu et al, 2018 ). Since SUMOylation of target proteins has been posited as an important factor in the pathogenesis or progression of PD, we assessed the effect of SUMOylation on α-syn for preventing its protein aggregation.…”
Section: Introductionmentioning
confidence: 99%